Vpliv gibljivosti ledvenega dela hrbtenice in kolka na prisotnost bolečin pri športno aktivni populaciji - Kambič, Tim (Šport (Ljubljana), 2018)
Low back pain presents a global health burden with increasing prevalence in sedentary as well as sport population. The aim of this study was to assess the prevalence of low back pain and its associations with altered lumbar spine posture, flexibility and mobility in lumbar spine and hips. A total of 96 sport active participants from four different sports disciplines were randomly included into the prospective study, aged 26,9 +- 6,9 years. We assessed alterations, flexibility and mobility of lumbar spine and hips with the wall test, goniometry, Schoeber`s test and functional measurement system, respectively. The pain was assessed with low back pain questionnaire for athletes. There were no significant correlation between low back pain and anatomic alterations of lumbar spine or the flexibility, neither did higher degree of pain affect the functional performance in selected FMS tests. However, a low but significant correlation was obtained between higher degree of low back pain and decreased external hip rotation (p = 0,031). In our study the selected clinical tests failed to objectively assess the relations with low back pain, therefore we suggest more systemic approach both in science and practice in order to lower the prevalence of this global health problem.
Keywords: biomehanika; bolečine v križu; gibljivost; ledvena hrbtenica; športniki